Kidney Disease detection and classification from CT Images using Watershed Segmentation and Deep Learning. - Hossain, Mohammad Sakib; Hassan, S.M. Nazmul; rahaman, Md. Nakib; Al-Amin, Mohammad; Hossain, Rakib (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.